METODE POHON GABUNGAN: SOLUSI PILIHAN UNTUK MENGATASI KELEMAHAN POHON REGRESI DAN KLASIFIKASI TUNGGAL - Bagus Sartono; Utami Dyah Syafitri (FORUM STATISTIKA DAN KOMPUTASI, 2010)
Classification and regression tree has been a widely used tool in various applied fields due to its capability to give excellent predictive analysis. Later on, ensemble tree appeared to enhance simple tree analysis and deals with some of the weakness found in simple techniques. The ensemble tree basically combines predictions values of many simple trees into a single prediction value. This paper is intended as an introductory article to give a brief overview of the available ensemble tree methods which might be found in detail in a variety of reading materials.